ANALYSIS OF TRANSLATION TECHNIQUE AND TRANSLATION QUALITY OF MARVEL COMICS ‘CIVIL WAR : WHOSE SIDE ARE YOU ON? PART 1, 2’ (MULTIMODAL APPROACH) - Rifqi Barezzi; M.R. Nababan; Riyadi Santosa (Universitas Sebelas Maret, 2019)
The objectives of this study are: (1) to know the translation techniques into on the Marvel Comic series 'CIVIL WAR: WHOSE SIDE ARE YOU ON?' PART 1, 2; and (2) to know the assessment of translation techniques on translation quality into on the Marvel Comic series 'CIVIL WAR: WHOSE SIDE ARE YOU ON?' PART 1, 2; (3) to know the multimodal (verbal and visual) approach. This study applies the multimodal approach to help the researcher masters the assessment of translation quality on the Marvel Comic series 'CIVIL WAR: WHOSE SIDE ARE YOU ON?' PART 1, 2 that had been translated in Bahasa Indonesia. Concerning on that, the researcher attempts to understand some techniques of translating, concepts of comic, and multimodal such verbal and visual for his theoretical framework. This study also belongs to the qualitative research which means that this research no needs any statistical value to generalize findings of the research. Even if there are any values of numbers found in this research, it just become the assessment to know the quality of translation of Marvel Comic series 'CIVIL WAR: WHOSE SIDE ARE YOU ON?' PART 1, 2 in Bahasa Indonesia, as it has become most important elements to this research because of it had been chosen as the source of data to the research.